THE USE OF SONGS IN TEACHING STUDENTS’ LISTENING ABILITY - Apin Hidayat (Journal of English and Education, 2013)
This study was aimed at first investigating whether or not the use of songs significantly improves students’ listening skill. Second, the difficulties faced bythe students in listening comprehension were also investigated. This quasiexperimentalresearch involved two classes of students of a public junior high schoolin Sumedang. The data were collected through pretest, posttest and questionnaires. Inanalyzing the collected data, quantitative research method was employed.Furthermore, the data taken from questionnaires were also investigated to find out thedifficulties faced by the students listening comprehensions through songs. The studyfound that the use of songs likely improves students’ listening comprehension skills. It was evidenced by tobt (6.542) that greater than tcrit. As the result of the study, the null hypothesis of thisresearch was rejected; the use of songs is likely to improve the students’ listeningcomprehension skill. Keywords:Songs, Listening Comprehension, Independent Sample t-test, PairedSample t-test